2007
DOI: 10.1590/s1516-35982007000300018
|View full text |Cite
|
Sign up to set email alerts
|

Influência da monensina sódica no consumo e na digestibilidade de dietas com diferentes teores de proteína para ovinos

Abstract: Foram alojados 25 ovinos castrados em gaiolas para estudos de metabolismo por 20 dias com o objetivo de determinar a influência da monensina na digestibilidade de dietas formuladas com diferentes teores de proteína. As dietas foram compostas de 11,4 e 16,5% de PB na MS, sendo constituídas de 65% de feno de capim-braquiária (Brachiaria decumbens) e 35% de concentrado, com inclusão ou não de 28 mg de monensina/kg de MS consumida, totalizando quatro dietas experimentais e uma composta apenas de feno puro. O conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
2
9
0
8
Order By: Relevance
“…A similar result was found by Oliveira et al (2007), who suggested a correlation between excess ammonia in the rumen and excess urea in the liver tissue, with a consequent reduction in salivary nitrogen recycling and the elimination of excess nitrogen by the kidneys through the urine. In the present study, there was no negative NB, nor were there differences in retained N/ingested N or retained N/absorbed N between treatments, thus indicating that the CP intake met the requirements of the animals.…”
Section: Nitrogen Balance (Nb) and Microbial Efficiencysupporting
confidence: 85%
“…A similar result was found by Oliveira et al (2007), who suggested a correlation between excess ammonia in the rumen and excess urea in the liver tissue, with a consequent reduction in salivary nitrogen recycling and the elimination of excess nitrogen by the kidneys through the urine. In the present study, there was no negative NB, nor were there differences in retained N/ingested N or retained N/absorbed N between treatments, thus indicating that the CP intake met the requirements of the animals.…”
Section: Nitrogen Balance (Nb) and Microbial Efficiencysupporting
confidence: 85%
“…Crude brown propolis promoted higher EE digestibility compared with monensin sodium (Table 4). Oliveira et al (2007) did not observe any effect of monensin sodium inclusion at 28 mg/kg DM in lamb diets with a 65:35 roughage:concentrate ratio. Prado et al (2010) observed a reduction in EE digestibility in cattle supplemented daily with 2.0 g of freeze-dried propolis extract/animal and attributed this response to the inhibition of rumen-lipolytic microorganisms.…”
Section: Discussionmentioning
confidence: 59%
“…Borges et al (2008) also obtained a non-significant increase in the digestibility coefficient of ruminally cannulated cows of 66.4% vs 60.4% for treatment with monensin and control, respectively. Zeoula et al (2008) found an increase of 8% in AD of DM with the use of monensin, and an increase in total digestibility of CP in the intestine, while Oliveira et al (2007) did not obtain alterations in the digestibility of DM and nutrients for sheep supplemented with monensin. Ionophores regularly have the action of increasing the digestibility of DM and starch in food based on grains, because there is a decrease in food intake; consequently, ruminal microflora have more time for digestion, considering the decrease in the rate of passage (RUSSELL; HOULIHAN, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Such increases can be explained by the increase in metabolizable energy of the feed. According to Oliveira et al (2007), higher fat deposition may be due to an increase in the total production of short chain fatty acids, concomitant with a reduction in methane production.…”
Section: Resultsmentioning
confidence: 99%